Cooperation and competition dynamics of business networks: A strategic management perspective - Sascha Albers (University of Cologne, Department of Business Policy and Logistics, 2013)
Business networks are cooperative entities formed by more than two firms in order to generate competitive advantages for each member. They often operate in dynamic contexts to which they need to adapt. Some of these dynamics result from other business networks' actions of adaptation and strategic maneuvering, constituting forms of competition between such networks. This chapter introduces three specific forms of such competition: (1) competition in network formation, (2) competition in network composition, and (3) competition in network governance; it explains each of these network competition forms, presents one exemplary research study for each and suggest implications for network and corporate management.
Keywords: 650; Cooperative Strategy; Multilateral Alliances; Strategic Management; Network Dynamics; Network Competition